Mindfulness-Based Stress Reduction, Fear Conditioning, and The Uncinate Fasciculus: A Pilot Study - Hölzel, Britta K.; Brunsch, Vincent; Gard, Tim; Greve, Douglas N.; Koch, Kathrin; Sorg, Christian; Lazar, Sara W.; Milad, Mohammed R. (Frontiers in Behavioral Neuroscience, 2016)
Mindfulness has been suggested to impact emotional learning, but research on these processes is scarce. The classical fear conditioning/extinction/extinction retention paradigm is a well-known method for assessing emotional learning. The present study tested the impact of mindfulness training on fear conditioning and extinction memory and further investigated whether changes in white matter fiber tracts might support such changes. The uncinate fasciculus was of particular interest in the context of emotional learning. In this pilot study, 46 healthy participants were quasi-randomized to a Mindfulness-Based Stress Reduction (MBSR, N=23) or waitlist control (N=23) group and underwent a two-day fear conditioning, extinction learning, and extinction memory protocol before and after the course or control period. Skin conductance response data served to measure the physiological response during conditioning and extinction memory phases. Diffusion tensor imaging data were analyzed with probabilistic tractography and analyzed for changes of fractional anisotropy in the uncinate fasciculus. During conditioning, participants were able to maintain a differential response to conditioned vs not conditioned stimuli following the MBSR course (i.e., higher sensitivity to the conditioned stimuli), while controls dropped the response. Extinction memory results were not interpretable due to baseline differences. MBSR participants showed a significant increase in fractional anisotropy in the uncinate fasciculus, while controls did not (group by time interaction missed significance). Pre-post changes in uncinate fasciculus were correlated with changes in the response to the conditioned stimuli. The findings suggest effects of mindfulness practice on the maintenance of sensitivity of emotional responses and suggest underlying neural plasticity. (ClinicalTrials.gov, Identifier NCT01320969, https://clinicaltrials.gov/ct2/show/NCT01320969).